Malaria burden in a birth cohort of HIV-exposed uninfected Ugandan infants living in a high malaria transmission setting - Abel Kakuru (Malaria Journal, 2016)
Abstract Background HIV-exposed, uninfected (HEU) infants suffer high morbidity and mortality in the first year of life compared to HIV-unexposed, uninfected (HUU) infants, but accurate data on the contribution of malaria are limited. Methods The incidence of febrile illnesses and malaria were evaluated in a birth cohort of HEU infants. Infants were prescribed daily trimethoprim–sulfamethoxazole (TS) prophylaxis from 6 weeks of age until exclusion of HIV-infection after cessation of breastfeeding. Infants were followed for all illnesses using passive surveillance and routine blood smears were done monthly. Malaria was diagnosed as a positive blood smear plus fever. Placental malaria was determined by histopathology, placental blood smear and PCR. Risk factors for time to first episode of malaria were assessed using a Cox proportional hazards model. Malaria incidence among HEU infants aged 6–12 months was compared to that in other cohorts of HEU and HUU infants from the same region. Results Among 361 HEU infants enrolled, 248 completed 12 months of follow-up resulting in 1562 episodes of febrile illness and 253 episodes of malaria after 305 person-years of follow-up. The incidence of febrile illness was 5.12 episodes per person-year (PPY), ranging from 4.13 episodes PPY in the first 4 months of life to 5.71 episodes PPY between 5 and 12 months of age. The overall malaria incidence was 0.83 episodes per person-year (PPY), increasing from 0.03 episodes PPY in the first 2 months of life to 2.00 episodes PPY between 11 and 12 months of age. There were no episodes of complicated malaria. The prevalence of asymptomatic parasitaemia was 1.2 % (19 of 1568 routine smears positive). Infants born to mothers with parasites detected from placental blood smears were at higher risk of malaria (hazard ratio = 4.51, P < 0.001). HEU infants in this study had a 2.4- to 3.5-fold lower incidence of malaria compared to HUU infants in other cohort studies from the same area. Conclusion The burden of malaria in this birth cohort of HEU infants living in a high-transmission setting and taking daily TS prophylaxis was relatively low. Alternative etiologies of fever should be considered in HEU-infants taking daily TS prophylaxis who present with fever. Trial Registration NCT00993031, registered 8 October, 2009